Modeling of separated flows near a suction slot - Logachev, I.N.; Logachev, K.I.; Averkova, O.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
In the framework of the ideal fluid flow theory, the screen effect on the aerodynamic drag of the suction flow is studied. The screen is situated in parallel to the plane of a suction slot built into a plane infinite wall. The work was supported by the Russian Foundation for Basic Research (project 08-08-13687-ofi_c) and by the Council under the President of the Russian Federation (project MK-2729.2010.8).